Cockle shell-derived nano carrier for Ara-C in the treatment of acute myeloid leukaemia - Ghaji, Mustafa Saddam (2018)
Leukemia is a cancerous disease of bone marrow and blood in which acute form progresses more rapidly than the chronic form. The major therapeutic approaches of different cancer types are limited to conventional chemotherapy such as (Ara-C) which suffers less specific, high toxicity and short half-life, multidrug resistance and selectivity, narrow therapeutic index and significant increases in high dose distribution to healthy cells or tissues. Targeting anticancer drug delivery system has the potential to overcome these significant drawbacks by improving chemotherapy drug efficacy, specific tumor targeting, enhance accumulation in tumor tissues or cells and minimize the systemic toxicity. Nanoparticles as drug delivery system enable unique approaches to cancer treatment. Over the last two decades, a large number of nanoparticle delivery systems have been developed for cancer therapy including organic and inorganic materials. Cockle shells (Anadara granosa) are found to be a rich natural resource for calcium carbonate aragonite. In this study, the cockle shell-derived calcium carbonate aragonite nanoparticles (CCANPs) were used as a carrier for Cytarabine (Ara-C) as a unique approach for cancer treatment. Nanoparticles were spherical-shaped when CCANPs was synthesized using the combination of chemical and mechanical method. The morphology and compositions of the products were characterized by Field Emission Scanning Electron Microscope (FE-SEM), Transmission Electron Microscope (TEM), Energy Dispersive X-ray (EDX), X-Ray Diffraction (XRD), Fourier Transform Infra-Red (FT-IR) and zeta potential. The anti-leukemia drug (Ara- C) was loaded into CCANPs. The spectrophotometer was used with a wavelength UVinvisible, to estimate the amount of loading and release profile of Ara-C. The results showed that the drugs (Ara-C) could be efficiently loaded into the CCANPs, and furthermore, the fast and sustained release of Ara-C was observed from the nanocarriers at pH 4.8 and slow release at pH 7.4, which shows pH-dependent properties. The nanoparticles were used as a carrier against HL-60 human leukemia cells (in vitro study) and for cancer therapy in a murine xenograft model (SCID mice) (in vivo study). The in vitro evaluation showed IC50 values upon 72 hours of treatment with pure Ara-C was 5μg/mL, and Ara-C loaded CCANPs was 2.5μg/mL. Apoptosis was demonstrated by Cell Counting Reagent (SF), Flow Cytometry (FCM), Methylene blue (MB) and Fluorescent Microscope (FM) where apparently cellular uptake of Ara-C/CCANPs through endocytosis indicating a dose and time-dependent response relationship. Morphological observations by SEM revealed microvilli disappearance, cell shrinkage, membrane blebbing and the formation of apoptotic bodies, which confirmed both Ara-C and half dose of Ara- C/CCANPs induced apoptosis of HL-60 cells. In brief, Ara-C loaded CCANPs are more effective than pure Ara-C to human leukemia (HL-60) cells. In vivo study revealed that CCANPs nanocarrier significantly enhances the effects of Ara-C on AML through blood smear, bone marrow smear and histopathological survey for vital organs (heart, liver, lung, spleen and kidney) for severe combined immunodeficient (SCID) mice. The pharmacokinetic study showing significant effect between pure Ara-C 50mg/kg group, 100mg/kg CCANPs loaded with 50mg/kg Ara-C and half dose of loaded drug (25/50 mg/kg), the rate of release of the drug in the plasma was slow in the two groups of the drug-loaded compared to the pure drug. The study revealed a new biodegradable, biocompatible, non-toxic to health and pH-sensitive, CCANPs with a feasible promising potential for targeted delivery carriers of antitumor drugs. The results established strong evidence that CCANPs has excellent properties that make it an ideal candidate for biological drug delivery systems.